The neutron and its role in cosmology and particle physics - Dubbers, Dirk; Schmidt, Michael G. (Reviews of modern physics, 2011)
Experiments with cold and ultracold neutrons have reached a level of precision such that problems far beyond the scale of the present standard model of particle physics become accessible to experimental investigation. Because of the close links between particle physics and cosmology, these studies also permit a deep look into the very first instances of our Universe. First addressed in this article, in both theory and experiment, is the problem of baryogenesis, the mechanism behind the evident dominance of matter over antimatter in the Universe. The question of how baryogenesis could have happened is open to experimental tests, and it turns out that this problem can be curbed by the very stringent limits on an electric dipole moment of the neutron, a quantity that also has deep implications for particle physics. Then the recent spectacular observation of neutron quantization in the Earth’s gravitational field and of resonance transitions between such gravitational energy states is discussed. These measurements, together with new evaluations of neutron scattering data, set new constraints on deviations from Newton’s gravitational law at the picometer scale. Such deviations are predicted in modern theories with extra dimensions that propose unification of the Planck scale with the scale of the standard model. These experiments start closing the remaining “axion window” on new spin-dependent forces in the submillimeter range. Another main topic is the weak-interaction parameters in various fields of physics and astrophysics that must all be derived from measured neutron-decay data. Up until now, about 10 different neutron-decay observables have been measured, much more than needed in the electroweak standard model. This allows various precise tests for new physics beyond the standard model, competing with or surpassing similar tests at high energy. The review ends with a discussion of neutron and nuclear data required in the synthesis of the elements during the “first three minutes” and later on in stellar nucleosynthesis.